2019
DOI: 10.1007/s00429-019-01940-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell numbers, distribution, shape, and regional variation throughout the murine hippocampal formation from the adult brain Allen Reference Atlas

Abstract: Quantifying the distribution of cells in every brain region is fundamental to attaining a comprehensive census of distinct neuronal and glial types. Until recently, estimating neuron numbers involved time-consuming procedures that were practically limited to stereological sampling. Progress in open-source image recognition software, growth in computing power, and unprecedented neuroinformatics developments now offer the potentially paradigm-shifting alternative of comprehensive cell-by-cell analysis in an enti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 86 publications
3
19
0
Order By: Relevance
“…As we have previously shown that γH2AX immunoreactive nuclei were widely distributed in numerous cortical areas including the primary and second auditory, motor, somatosensory and visual cortices—see Figure 1 in [ 13 ]—we were not interested in exploring differences among cortical areas in more depth. Also, our assessments in the hippocampus are consistent with the literature (Table 3 from [ 76 ], and data from the Allen Brain Atlas [ 77 ]). We found no literature data on the volumetric density of SVZ/RMS/OB cells that could be useful to compare with our current estimation.…”
Section: Determination Of γH2ax Primary Antibodies Reactivenesssupporting
confidence: 88%
See 1 more Smart Citation
“…As we have previously shown that γH2AX immunoreactive nuclei were widely distributed in numerous cortical areas including the primary and second auditory, motor, somatosensory and visual cortices—see Figure 1 in [ 13 ]—we were not interested in exploring differences among cortical areas in more depth. Also, our assessments in the hippocampus are consistent with the literature (Table 3 from [ 76 ], and data from the Allen Brain Atlas [ 77 ]). We found no literature data on the volumetric density of SVZ/RMS/OB cells that could be useful to compare with our current estimation.…”
Section: Determination Of γH2ax Primary Antibodies Reactivenesssupporting
confidence: 88%
“…Also, our assessments in the hippocampus are consistent with the literature (Table 3 from [76], and data from the Allen Brain Atlas [77]).…”
supporting
confidence: 89%
“…Further, BLA.am cell bodies are 20% taller, 30% wider, and more spherical than BLA.ac neurons. While these differences are unlikely to affect computational functions, they could be useful features for future automated high-throughput cell identification 33 .…”
Section: Resultsmentioning
confidence: 99%
“…To further improve our ilastik segmentations, we implemented a post-processing step for the manual removal of erroneously segmented objects. To convert profile counts into cell number estimates for entire regions, it is necessary to address several sources of bias ( Attili et al., 2019 ). First, when the brain is cut into sections, some cells are split and can therefore appear in more than one section, which may lead to overcounting.…”
Section: Discussionmentioning
confidence: 99%